PATIENT IDENTIFICATION IMPLEMENTATION IN WARD BASED ON NURSES' KNOWLEDGE AND ADHERENCE [PELAKSANAAN IDENTIFIKASI PASIEN DI RUANG RAWAT INAP BERDASARKAN PENGETAHUAN DAN KEPATUHAN PERAWAT] - Brigitta Rahayu Dian Pratiwi; Elisa Natalia; Immaria Verolita Tanasale; Renata Komalasari (Nursing Current: Jurnal Keperawatan, 2019)
Making errors in patient identification can cause problems and are threats to safety of patients. Nurses’ adequate knowledge and adherence to the implementation of patient identification can improve patient safety. This study used quantitative research with correlation research design. This study was conducted in the inpatient unit at a private hospital in western Indonesia with a total of 37 nurses. Data were collected using questionnaires developed and has been tested for validity and reliability. Observations were also carried out to directly observe the nurses’ behaviors in carrying out patient identification using checklist observation guide developed from the standard operational procedures of the hospital. Data were analyzed using both univariate and bivariate tests with Spearman Rank. The results of this study showed significant correlation between level of nurse’s knowledge and adherence in implementing patient identification correctly with patient identification implementation (p value = 0.049). Based on the observation of the nurses in the ward showed no significant correlation between level of knowledge and adherence and implementation of patient identification by nurses (p value = 0.159). The results of the observation of nurses was contrary to the study results collected from questionnaire that measure nurses’ adherence, thus further research is needed to identify factors that effect nurses’ adherence in implementing patient identification in in-patient unit.BAHASA INDONESIA Kesalahan melakukan identifikasi pasien dapat menimbulkan masalah dan ancaman keselamatan pada pasien. Pengetahuan dan kepatuhan perawat yang adekuat dalam melaksanakan identifikasi pasien dapat meningkatkan keselamatan pasien. Penelitian ini menggunakan penelitian kuantitatif desain korelasi, dilakukan pada bulan Juli diruang rawat salah satu Rumah Sakit Swasta di Indonesia Barat dengan jumlah responden 37 perawat. Alat yang digunakan adalah kuesioner yang sudah diuji validitas dan reliabilitas untuk mengukur pengetahuan dan kepatuhan. Serta lembar panduan observasi berupa checklist observasi yang dikembangkan dari Standar Prosedur Operasional, untuk mengamati perilaku perawat mengidentifikasi pasien di ruang rawat inap. Data dianalisis menggunakan uji univariat dan uji bivariat dengan uji korelasi Spearman Rank. Uji korelasi Spearman Rank menunjukkan ada hubungan signifikan bersifat lemah antara tingkat pengetahuan dan kepatuhan perawat berdasarkan kuesioner (p=0,049). Berdasarkan observasi, tidak ada hubungan antara pengetahuan dan kepatuhan perawat (p=0,159). Hasil penelitian ini bertolak belakang dengan kepatuhan perawat dalam melakukan identifikasi pasien, yang diukur dengan kuesioner. Penelitian selanjutnya dapat meneliti faktor yang memengaruhi ketidakpatuhan perawat dalam melakukan pelaksanaan identifikasi pasien di ruang rawat inap.